2004
DOI: 10.1002/dvdy.20183
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐11 signaling is required for the differentiation of natural killer cells at the maternal–fetal interface

Abstract: Interleukin-11 (IL-11

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 40 publications
0
36
1
Order By: Relevance
“…Binucleate uNK cells, representing senescent cells (39), were also significantly increased. This finding contradicts a previous report on IL11Rα −/− mice, in which IL15 production was compromised and uNK cell localization within the decidual compartment was virtually absent (40). Together, these findings suggest that IL11 signaling is required for normal uNK cell recruitment, but elevated levels also affect recruitment and/or differentiation and normal function.…”
Section: Discussioncontrasting
confidence: 95%
“…Binucleate uNK cells, representing senescent cells (39), were also significantly increased. This finding contradicts a previous report on IL11Rα −/− mice, in which IL15 production was compromised and uNK cell localization within the decidual compartment was virtually absent (40). Together, these findings suggest that IL11 signaling is required for normal uNK cell recruitment, but elevated levels also affect recruitment and/or differentiation and normal function.…”
Section: Discussioncontrasting
confidence: 95%
“…uNKC deficiencies were previously found in IL-15 Ϫ/Ϫ mice that have residual amounts of improperly developed NKC (71) and in IL-11 Ϫ/Ϫ or Hoxa-10 Ϫ/Ϫ mice bearing developmentally impaired deciduae (72,73). However, T-bet Ϫ/Ϫ mice that have an overall reduction in NKC number do contain normal numbers of uNKC (71).…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, recent evidence in mice shows that IL11 signaling is required for decidual-specific maturation of NK cells. It has also been suggested that defective decidual vasculature is present in the IL11Ra mutant uterus compared with wild-type mice (Ain et al 2004). As for human, increasing evidence indicates that IL11 has an important function in implantation.…”
Section: Interleukin 11mentioning
confidence: 99%